Metal-organic frameworks as solid Brønsted acid catalysts for advanced organic transformations - Gong, Wei; Liu, Yan; Li, Haiyang; Cui, Yong (Coordination chemistry reviews, 2020)
[Display omitted] •Design and synthesis strategies of Brønsted acidic MOFs are summarized.•Various types of organic reactions with Brønsted acidic MOFs are presented.•The challenges and opportunities of Brønsted acidic MOFs for organic transformations are discussed. Solid Brønsted acid catalysts, an important class of heterogeneous catalyst, are emerging as an ideal alternative to conventional liquid mineral acids in promoting diverse proton-catalyzed organic transformations in respect of green and sustainable chemistry. In particular, benefitting from the astonishing structural diversity, exceptional porosity as well as high modularity and tunability, Brønsted acidic metal-organic frameworks (BA-MOFs) have been extensively recognized as prominent candidates, which distinguished them from traditional solid Brønsted acids. In this paper, we summarize the recent advances of BA-MOF materials, including the design and synthesis, and their catalytic behavior in various organic transformations. The insights into the challenges and outlook on the future research direction of the field are also presented.